Romantic Periodicals and Print Culture. - Behrendt, Stephen C., 1947- (Taylor & Francis, 2003)
The essays in this collection treat periodical writing as intrinsically worthy of attention not a mere backdrop to the emergence of British Romanticism but a site in which Romantic ideals were challenged, modified, and developed.